A novel combined Hib-MenC-TT glycoconjugate vaccine as a booster dose for toddlers: a phase 3 open randomised controlled trial. Issue 11 (7th May 2008) - Pace, D; Snape, M; Westcar, S; Oluwalana, C; Yu, L-M; Begg, N; Wysocki, J; Czajka, H; Maechler, G; Boutriau, D; Pollard, A J
Abstract : Objective: To study the immunogenicity and reactogenicity of a combined Haemophilus influenzae type b and Neisseria meningitidis serogroup C tetanus toxoid conjugate vaccine (Hib-MenC-TT) when administered as a booster dose in combination with a measles, mumps and rubella vaccine (MMR). Design: A phase 3 open randomised controlled trial. Setting: One centre in Oxford, UK and nine centres in Poland. Subjects: 12–15-month-old healthy children. Interventions: In the primary stage of the study 500 healthy 6–12-week-old infants were randomised in a 3:1 ratio to receive Hib-MenC-TT+DTPa-IPV or MenC-CRM197 vaccine+DTPa-IPV-Hib. In the booster stage, 476 participants (190 in the UK and 286 in Poland) were vaccinated with Hib-MenC-TT and MMR. Main outcome measures: The proportion of children with protective serum antibody levels against MenC and Hib 6 weeks following a Hib-MenC-TT booster dose. Results: The co-primary objectives were met: the Hib-MenC-TT booster dose induced protective antibody titres in children vaccinated with Hib-MenC-TT+DTPa-IPV or MenC-CRM197+DTPa-IPV-Hib at 2, 3 and 4 months of age. 94.8% (lower limit of (LL) 95% CI 92.4) of participants had rSBA-MenC ⩾1:128 and 100% (LL 95% CI 99.2) achieved anti-PRP concentrations ⩾1.0 μg/ml. The percentage of toddlers with a post boost rSBA-MenC of 1:128 was significantly higher after priming with Hib-MenC-TT (97.7%) than after MenC-CRM197 (86%) (difference: 11.7%; 95% CI 6.2 to 19.4). Conclusion: The waning antibody titres against Hib and MenC following primary immunisation can be boosted to protective levels by administering the Hib-MenC-TT vaccine at 12–15 months of age, supporting the recent introduction of this vaccine in the UK immunisation schedule to sustain protection of children against Hib and MenC disease. Trial registration number: NCT00258700. Study ID: 103974 (http://clinicaltrials.gov ).